2018
DOI: 10.1007/s12016-018-8706-z
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Hand Dermatitis: a Practical Approach

Abstract: Occupational skin disease is common. It affects workers more often than reported. Contact dermatitis, both irritant and allergic, accounts for the majority of occupational skin diagnoses. Occupational contact dermatitis (OCD) frequently affects the hands and may have a profound impact on an employee's ability to perform a job. Severe OCD can affect a worker's activities of daily living and can even lead to job loss. Numerous irritants have been described in the workplace, from the common (wet work) to the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 63 publications
5
66
0
6
Order By: Relevance
“…Regarding the diagnosis, we find that ACD is predominant in our population (56.5% vs 43.5%) with a slightly higher proportion, as compared to ICD, among individuals with OCD (OR 1.14; 95%CI 1.04–1.26). Generally, ICD is the most common type of CD reported in literature, accounting for 60–80% of all CD, while ACD accounts for the remaining 20–40%, 6,41,51 but the proportion may vary widely across studies, depending on the occupations that prevail and the hazards to which people are exposed, the centers that report cases, and differences in the diagnostic criteria 4,5,52,53 . In comparison, a previous Italian study from Sertoli et al found that ACD clearly predominates over ICD (64,4% vs 34,6%, respectively) 14 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Regarding the diagnosis, we find that ACD is predominant in our population (56.5% vs 43.5%) with a slightly higher proportion, as compared to ICD, among individuals with OCD (OR 1.14; 95%CI 1.04–1.26). Generally, ICD is the most common type of CD reported in literature, accounting for 60–80% of all CD, while ACD accounts for the remaining 20–40%, 6,41,51 but the proportion may vary widely across studies, depending on the occupations that prevail and the hazards to which people are exposed, the centers that report cases, and differences in the diagnostic criteria 4,5,52,53 . In comparison, a previous Italian study from Sertoli et al found that ACD clearly predominates over ICD (64,4% vs 34,6%, respectively) 14 .…”
Section: Discussionmentioning
confidence: 94%
“…The incidence rates reported so far underestimate the actual frequency of the phenomenon due to underdiagnosis and underreporting 5,6,8,10,12 . The most reliable studies provided a range of estimates of 11 to 86 cases/100000 workers per year, depending on the country 5‐7 …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…48,49 CD is mostly located on the hands, followed by the face (for airborne contamination, secondary contact through hands, or by direct exposure, ie, make-up), as those parts of the body are most exposed to external agents. 50 Hands and forearms are the most common sites of OCD in manual workers who are exposed to water, detergents, solvents, irritants, and sensitizers, as are hairdressers. 7,44,51 The prevalence of hand dermatitis in hairdressers in the present study (55.6%) is within the same range found in previous investigations.…”
Section: Discussionmentioning
confidence: 99%